MORPHOLOGICAL CHARACTERISTICS OF THE PLACENTA IN PATIENTS WITH HEM LOSS SYNDROME IN WOMEN WITH THROMBOPHILIA - Saidzhalilova , D.D.; Nizamova, M.Sh. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
The aim is to analyze the morphological characteristics of the placenta, including the causes of its development, clinical significance, and risks to women’s health in patients with hem loss syndrome in women with thrombophilia. Research materials and methods: For morphological examination, placentas were taken from 48 women who had a late spontaneous miscarriage during pregnancy from 13 to 20 weeks. Morphological studies of the placenta were conducted at the Department of Normal, Pathological Physiology and Pathological Anatomy of the Tashkent Medical Academy. Research results: Of the 8 cases in which miscarriage occurred at 13-16 weeks, 6 had signs of placental vascular thrombosis, and 5 had placental immaturity. At the same time, during histological examination, terminal chorionic villi prevailed in the preparations, very closely adjacent to each other, with the disappearance of the interstitial space and the deposition of fibrin (Fig. 1), and the accumulation of inflammatory cells is noted in the decidual tissue (Fig.2), the stroma of the terminal villi and the interstitial space. Blood vessels are located mainly in the central area of the villi, and in a significant part they are not detected. In part of the observations (3 out of 8), edema of the terminal or stem villi is noted, with abnormally developed capillaries. In the hotel areas, the terminal villi are glued together with a large number of syncytial buds. Conclusion: Summing up the study of the placentas of women with miscarriage at 13-16 weeks of gestation, it can be concluded that the morphological picture corresponds to the signs of placental insufficiency, with the presence of varying degrees and localization of thrombosis and inflammation. In the group of women with termination of pregnancy at 13-16 weeks of gestation, the detected changes in hemostasis did not have statistically significant differences from those in the control group, although it is necessary to note a tendency to increase the concentration of fibrinogen and an increase in the phenanthroline test.